The Ability of the Thermophilic Bacteria Triculture Consortium from Mudiak Sapan Hot Springs to Produce Biofuel - Irdawati Irdawati; Putri Rachma Auliya; Dwi Hilda Putri; Dezi Handayani; Yusrizal Yusrizal (Postgraduate, University of Mataram, 2023)
Biofuel is an alternative energy to replace fossil fuels. The most popular form of biofuel today is bioethanol. Biofuels are considered as a suitable alternative to fossil fuels because they are more environmentally friendly. Production of bioethanol utilizing thermophilic microorganisms is more profitable because thermophilic microbes generally have the characteristics of being able to use a variety of substrates, low contamination, and resistance to high temperatures. The use of microbial consortia tends to give better results than the use of monoculture isolates to optimize bioethanol yields. The aim of this study was to determine the compatibility and ability of the best thermophilic bacterial triculture consortium from the Mudiak Sapan hot springs in producing biofuel. This research is a descriptive research, to test isolates of a consortium of thermophilic bacteria that produce bioethanol. The results of this study showed that consortium isolates tended to give better results than monoculture isolates. The best thermophilic bacterial triculture consortium from the Mudiak Sapan hot springs in producing biofuels namely MS 12, 17, 18 produced a bioethanol content of 0.863%.